Case Study of Standard Nutritional Care Processes on Dyspepsia Patients in Seroja Pavilion Undata Palu Hospital: Studi Kasus Proses Asuhan Gizi Terstandar pada Pasien Dispepsia di Paviliun Seroja RSUD Undata Palu - Nurjaya Nurjaya; Putu Candriasih; Dhea Rizky Ananda (Poltekkes Kemenkes Palu, 2021)
Gastrointestinal diseases and several other Non-Communicable Diseases (NCDs) together cause as much as 30% of deaths. This study aims to conduct a case study of PAGT in dyspeptic patients at the Seroja Pavilion Class III UPT RSUD Undata Palu. This study is a case study with a sample of 1 dyspepsia patient. The data collected were data on eating habits, food intake, anthropometry, as well as the results of biochemical and clinical/physical examinations. Data collection techniques used primary data (data obtained from measurements and interviews) and secondary data (data collected from hospital reports and patient medical records). The results of this study were that the patient's food intake increased from <60% to 80%, the nutritional status of the patient was still thin (no change), normal HGB from 8.9 mg/dL to 11.9 mg/dL. Clinical/physical normal, complaints reduced, knowledge about nutrition and gastric diet increased, the patient began to try to change eating habits to become regular. Initial diagnoses were NI-2.1, NC-4.1, and NB-1.1, at the end of treatment the remaining diagnoses were NC-4.1 and there were no new nutritional diagnoses. The conclusion of this study is the initial assessment of the patient's nutritional intake deficit, poor nutritional status, low Hb, and complaints of nausea and abdominal pain. The final diagnosis was NC-1.4. The nutritional interventions provided were Gastric Diet II and nutrition education. The results of monitoring and evaluation of patients experienced many good changes in food intake as well as knowledge and behavior. There was no reassessment of the patient.